(untitled) (Journal of Oriental Studies, 2023)
This study reveals the characteristics of the Koreans’ view of death formed in historical and religious contexts by analyzing the ancient literature that shows the Koreans’ view of life and death well after the Three Kingdoms period. Koreans’ thoughts and values of death have changed greatly under the influence of popular religions and ideologies in each era. Based on the original indigenous beliefs, it has been complexly formed by the beliefs constantly imported from outside, and by the Buddhist and Confucian ideas adopted as the state religions. Due to the influence of Confucianism, Koreans focus on the present life rather than afterlife, but at the same time, shamanistic remnants of death rituals and customs that value the afterlife by Buddhism remain. Keywords: Koreans, Perspective on death, Folk religion, Confucianism, Buddhism.